The Impact of the 2008 Global Financial Crisis on the Jordanian Banking Sector - Alqaisi, Fouzan (International Journal of Economics and Financial Issues, 2018)
Key aspects of the global financial crisis (GFC) need to be uncovered and comprehended further in order to investigate its impact on the wider global financial systems. The paper evaluates the impacts on the Jordanian banking sector since the financial market in Jordan is still underdeveloped and banks are the most important source of finance in the country. This would help to determine levels of stability and security within the Jordanian banking system. This paper aims to: (1) Investigate the roots and consequences of the 2008 GFC, and (2) explore whether this crisis affected the banking sector in Jordan or not. Data used from a sample of three Jordanian commercial banks during 2008 and 2010. The paper found that the crisis did not have major impacts on the Jordanian banking sector. Keywords: Global Financial Crisis, Banking Sector, Financial System, Jordan JEL Classifications: G01, G1, G2